An inheritance of poetry - Adshead, Gladys L.; Duff, Annis; Unwin, Nora Spicer, 1907- ([Boston] : Houghton Mifflin Co., 1948)
A collection of English and American poetry for all moods and all ages.
Keywords: English poetry; American poetry; English poetry -- Collections; American poetry -- Collections